The constraints and prospects of small scale business enterprises in Nigeria (2011)
Small businesses play a vital role in the economic development of any nation. They are a strategic sector for generating high economic growth, reducing unemployment and a veritable tool for poverty alleviation. Based on the current economic globalization and neo - liberalization concept, the paper examines the constraints and prospects of small business development in Nigeria. Exploring the concept of entrepreneurship, the paper asserts that the growth in small businesses will be proportionate to the level of entrepreneurship in the country. Thus the paper asserts further that the constraints of small business development are synonymous with the constraints to entrepreneurial development and identifies high interest rates of banks and financial institutions, defective educational curriculum that does not support entrepreneurship, influx of foreign products, weak enforcement of copyright and piracy laws as well as poor infrastructural support as major constraints to small business development in Nigeria. The paper concludes on an optimistic note by highlighting various economic and social conditions which offers hope and prospects to entrepreneurial and small businesses development in Nigeria such as the prevailing economic situation, renewed government support for small business development and the prevailing social scene in the country, which offer high incentives to business development.